Antibacterial Activity of N-Hexan and Ethyl Acetate Fractions of Gaharu Leaves (Aquilaria malaccensis) Against Bacteria Causing Skin Infection - Sompa, Putri Tenri; Herwin, Herwin; Fitriana, Fitriana (Fakultas Farmasi, Universitas Muslim Indonesia, 2024)
Gaharu (Aquilaria malaccensis) leaves are plants that are useful in the treatment of infectious diseases. This study aims to obtain n-hexane and ethyl acetate fractions of Gaharu leaves that have antibacterial activity against skin infection bacteria by agar diffusion. The results of antibacterial activity screening of the n-hexane fraction and ethyl acetate fraction at a concentration of 0.1% is bacteriostatic. The test results of Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) using concentrations of 0.1%, 0.2%, 0.4%, 0.8%, 1.6%, 3.2%, 6.4% and 12.8% obtained MIC value of n-hexane fraction at 0.2% against P. acnes, P. aeurogynes bacteria and 0.4% against S. aureus, S. epidermidis bacteria, MIC value of ethyl acetate fraction was 0.2% against P. aeuroginosa, S. aureus bacteria and 0.4% against P. acnes, S. epidermidis bacteria. MBC value of n-hexan fraction was 0.4% against P. acnes, P. aeuroginosa bacteria, 0.8% against S. aureus bacteria, 1.6% against S. epidermidis bacteria, MBC value of ethyl acetate fraction was 0.4% against P. acnes, P. aeuroginosa, S. aureus bacteria, 0.8% against S. epidermidis bacteria. The results of the antibacterial activity using concentrations of 1.56%, 3.12%, 6.25%, 12.5% and 25% obtained the largest inhibition zone diameter of the n-hexane fraction was 13,99 mm and the ethyl acetate fraction was 27,68 mm against S. epidermidis bacteria at a concentration of 25%. Based on the results, it can be concluded that the antibacterial activity of the ethyl acetate fraction against all test bacteria is stronger than the n-hexane fraction